Interfacial Engineering in Organic Photovoltaics: Enhancing Efficiency through Material Innovations - Xu, Xinyao (Highlights in Science, Engineering and Technology, 2024)
Interfacial engineering has emerged as a critical aspect of organic photovoltaic (OPV) devices. This paper’s comprehensive review explores the significant advancements in interfacial layer design and material innovations that have revolutionized the field of OPVs. By examining the advantages and impact of interfacial layers, the study highlights the crucial role of advanced materials such as conductive polymers, inorganic nanomaterials, and self-assembled monolayers in optimizing device performance. The review delves into engineering strategies, including energy level alignment, hybrid interfacial layers, and layer thickness and uniformity control, which have proven instrumental in overcoming challenges associated with charge transport and selectivity. Furthermore, the article discusses the future directions and emerging approaches in interfacial engineering, such as the exploration of two-dimensional materials, machine learning-assisted material discovery, and the development of multifunctional layers. By providing valuable insights into the cutting-edge technology and the remaining challenges, the review serves as a roadmap for researchers aiming to unlock the full potential of OPVs as a sustainable and efficient renewable energy technology.